(untitled) (Boston, 2007)
This anthology is designed to be a stand-alone text for an introduction to philosophy course. It includes more accessible readings, selected from general-readership magazines like Harper's, Lingua Franca, and Scientific American to help shape and give definition to the more difficult philosophical readings, like those of Plato, Aquinas, Locke, and Kant.
Keywords: Philosophy,Triết học